Consultations with patients for whom English is not their first language. Issue 6 (5th November 2019) - Turner, Benjamin; Madi, Heba
Abstract : Good communication is essential in neurological consultations, yet this is obviously compromised by the absence of a common language. Interpreters can make valuable contributions to improving consultations, but translation has its shortcomings. The consultation dialogue is not always interpreted correctly or accurately, even (or especially) when friends or family are translating. Clinicians should therefore try to ensure that key information has been communicated and understood, perhaps by repetition or asking the patient to say what they have understood. Cultural factors are also important in the patient–physician interaction. Physicians should try to adopt a culturally sensitive approach during consultations, familiarising themselves with cultural norms within the prevalent ethnic minority groups in their area. They should resist directive approaches to save time and try to involve the patient in decision-making. This requires allocating extra time to consultations with patients for whom English is not their first language.